Pengaruh Suhu Sintering Pada Pembuatan Strontium Titanat (SrTiO3) Terhadap Konstanta Dielektrik Menggunakan Metode Co-Precipitation - Husnah Rofiko; Yofentina iriani; Risa Suryana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Strontium Titanate (SrTiO3) with variation of sintering temperatures were prepared by co-precipitation methods. Sintering temperature were varied at 700oC, 800oC, and 900oC for 4 hours. SrTiO3 samples were prepared by Strontium Nitrate and Titanium Tetrabutoxide. SrTiO3 samples were characterized by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Resistance Capacitance Inductance (RCL) meter, and Sawyer Tower.  SEM images show that the sintering temperatures could affect the grain size of SrTiO3. In addition, crystal size of SrTiO3 (110) affected by sintering temperature. The highest of dielectric constant is 137 on SrTiO3 at sintering temperature of 900oC. Sawyer Tower curves confirmed that SrTiO3 has paraelectric property.Keyword: Strontium Titanate, Co-precipitation, dielectrics constant, paraelectrics